Effect of oral environment and prescribed fluoride mouthwashes on different types of TMA wires - An in-vivo study - Arun Rajendran; Shobha Sundareswaran; Latheef Vadakke Peediyekkal; Praveen Santhakumar; Sreehari Sathyanadhan (Wolters Kluwer Medknow Publications, 2019)
OBJECTIVE: The aim of this study was to investigate the effect of intraoral conditions and fluoride mouthwashes on mechanical properties and surface characteristics of different types of titanium molybdenum alloy (TMA) wires. MATERIALS AND METHODS: Three types of TMA wires of dimension 0.017" × 0.025" [1. Standard TMA (TMA), 2. ion-implanted, low-friction TMA (LF) and 3. Colored, Honey Dew TMA (HD)] were tested in three conditions as three groups; A) Control (as received), B) No fluoride (following intraoral use without fluoride) and C) Fluoride (following intraoral use with fluoride rinses). Surface roughness was evaluated using 3D Optical Profilometer. Three point bending tests were done to evaluate load deflection characteristics (LDR), ultimate tensile strength (UTS), and Young's modulus (E). Statistical evaluation was done using one-way analysis of variance (ANOVA), Bonferroni multiple comparison, and paired t-tests. RESULTS: Control group TMA exhibited significantly higher surface roughness, peak height, and LDR as well as lower UTS and E when compared to LF and HD (P < 0.001). In nonfluoride group, the surface roughness and LDR increased significantly for all three types of wires (P < 0.001). The UTS and E showed a significant decrease (P < 0.001). Additional use of fluoride mouthwashes (fluoride group) further increased surface roughness and LDR and decreased the UTS and E (P < 0.001). CONCLUSION: The ion-implanted LF/HD varieties had better surface smoothness, lower LDR, higher UTS, and higher E than standard TMA in the control group, pointing towards a better efficiency of these wires. Intraoral conditions significantly increased surface roughness and deteriorated mechanical properties of all types of TMA wires. With the use of daily fluoride mouthwashes, the deterioration was much worse.